Tobler’s first law in the digital economy based on the Internet of Everything: Priority issues - Viktor Ivanovich Blanutza (Вестник Пермского университета: Серия Экономика, 2023)
Introduction. W. Tobler, an American researcher, worded the first law of geography by linking the location with the interaction among economic agents. This produced spatial analysis and shaped spatial interactions in the pre-Internet era. However, the development of information and communication technologies doubted the significance of location and spatial distance in the emerging digital economy based on the Internet of People. Scientific discussions concerning this issue and empirical studies established that the modern digital economy, including the one derived from the Internet of Things, partially depends on the actual geographical space. In the next decade, further development of technologies could lead to a digital economy based on the Internet of Everything. Currently, there is no data about how spatially distributed economic agents will interact in the future digital world.